Referrals for MMR immunisation in hospital. Issue 8 (6th April 2010) - Ainsworth, Emma; Debenham, Philip; Carrol, Enitan D; Riordan, F Andrew I
Abstract : Concern exists about measles, mumps and rubella (MMR) vaccine in egg-allergic children, although this has been shown to be safe. Guidelines from the Royal College of Paediatrics and Child Health (RCPCH) and British Society of Allergy and Clinical Immunology (BSACI) suggesting which children should be referred to hospital for MMR, were published in 2000. We audited referrals to hospital for MMR against these guidelines. One hundred and ten children were referred for MMR to Birmingham Heartlands Hospital (2002–2004) and Alder Hey Children's Hospital (2006–2009). Eighty-two (75%) children did not meet the published criteria. Only 13 children (12%) had severe egg allergy. The first dose of MMR vaccine was delayed by >30 days in 81% of children. All children were given MMR, none had a significant reaction. Children with egg allergy do not need to be given MMR in hospital, but MMR is often delayed by unnecessary hospital referral. New BSACI guidelines encouraging MMR vaccination of egg-allergic children in primary care need to be disseminated.